Critical signaling pathways in osteoclast differentiation and bone resorption: mechanisms and therapeutic implications for periprosthetic osteolysis - Yin, Liangzi; Sun, Chenglin; Zhang, Junjie; Li, Yan; Wang, Yansheng; Bai, Lunhao; Lei, Zeming (Frontiers in Cell and Developmental Biology, 2025)
Bone homeostasis is dynamically regulated by the balance between osteoclast-mediated bone resorption and osteoblast-driven bone formation. Periprosthetic osteolysis (PPO), a major complication following joint arthroplasty, occurs when excessive bone resorption surpasses formation, leading to implant loosening and failure. Emerging evidence highlights the pivotal roles of the RANKL/RANK/OPG axis, nuclear factor-κB (NF-κB) signaling, and mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) cascades in osteoclast differentiation and pathological bone resorption. This review systematically explores the molecular mechanisms by which these pathways regulate osteoclastogenesis and their pathological contributions to PPO. Specifically, we analyze how wear particle-induced inflammation reprograms these signaling networks to exacerbate osteolytic activity. Furthermore, we discuss potential therapeutic strategies targeting these pathways, including pharmacological inhibitors, gene therapy, and dual-target interventions, to restore bone homeostasis. By integrating recent advances in osteoimmunology and translational research, this work provides a comprehensive framework for understanding PPO pathogenesis and developing precision therapies.